Influence of tribology on global energy consumption, costs and emissions - Kenneth Holmberg; Ali Erdemir (Friction)
Abstract Calculations of the impact of friction and wear on energy consumption, economic expenditure, and CO2 emissions are presented on a global scale. This impact study covers the four main energy consuming sectors: transportation, manufacturing, power generation, and residential. Previously published four case studies on passenger cars, trucks and buses, paper machines and the mining industry were included in our detailed calculations as reference data in our current analyses. The following can be concluded: In total, ~23% (119 EJ) of the world’s total energy consumption originates from tribological contacts. Of that 20% (103 EJ) is used to overcome friction and 3% (16 EJ) is used to remanufacture worn parts and spare equipment due to wear and wear-related failures. By taking advantage of the new surface, materials, and lubrication technologies for friction reduction and wear protection in vehicles, machinery and other equipment worldwide, energy losses due to friction and wear could potentially be reduced by 40% in the long term (15 years)and by 18% in the short term (8 years). On global scale, these savings would amount to 1.4% of the GDP annually and 8.7% of the total energy consumption in the long term. The largest short term energy savings are envisioned in transportation (25%) and in the power generation (20%) while the potential savings in the manufacturing and residential sectors are estimated to be ~10%. In the longer terms, the savings would be 55%, 40%, 25%, and 20%, respectively. Implementing advanced tribological technologies can also reduce the CO2 emissions globally by as much as 1,460 MtCO2 and result in 450,000 million Euros cost savings in the short term. In the longer term, the reduction can be 3,140 MtCO2 and the cost savings 970,000 million Euros. Fifty years ago, wear and wear-related failures were a major concern for UK industry and their mitigation was considered to be the major contributor to potential economic savings by as much as 95% in ten years by the development and deployment of new tribological solutions. The corresponding estimated savings are today still of the same orders but the calculated contribution to cost reduction is about 74% by friction reduction and to 26% from better wear protection. Overall, wear appears to be more critical than friction as it may result in catastrophic failures and operational breakdowns that can adversely impact productivity and hence cost.